Risk Analysis of E-Procurement Process of EPC Construction Project Based On Risk Management - Raditya Gusti Andaru; Tri Joko Wahyu Adi (Publikasi Indonesia, 2024)
EPC project performance is affected by the relation between work processes. E-procurement implemented as a tool to mitigate procurement process risk gives a positive effect and residual risk that needs to be managed further. This research aims to analyze the e-procurement process risk and identify the root causes of critical risks. Data is collected using Focus Group Discussion (FGD) and a questionnaire by 41 e-procurement practitioners from 5 (five) Indonesian construction state-owned enterprises (BUMN). There are 116 risks identified from 22 e-procurement steps, of which three risks are determined as critical risks based on Risk Priority Number analysis, with delay of material requisition document as the highest RPN risk. Fault Tree Analysis identifies that several failure modes, such as miscalculation, misallocation of workforce, and payment issues cause the critical risk. Preparing an in-house engineering team to support the calculation process can mitigate two critical risks at the same time. Risk mitigation causes a residual risk that needs further assessment to determine the proper response.